2019
DOI: 10.1002/cam4.1926
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening history prior to a diagnosis of cervical cancer in Danish women aged 60 years and older—A national cohort study

Abstract: The incidence and mortality of cervical cancer are high in Danish women aged 60 years and older who are about to exit the cervical cancer screening program. The present study aimed to describe the screening history in women ≥60 years old, diagnosed with cervical cancer in Denmark, 2009‐2013. We retrieved information on cases of cervical cancer and previous cervical cancer screening from national registries. During the study period, a total of 1907 women were diagnosed with cervical cancer, 574 (30.1%) of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…It should, however, be taken into account that after 50 years of screening, the current age-specific incidence of cervical cancer is no longer a pure reflection of the underlying risk of the disease, but it reflects also the screening history of the respective birth cohort. A study of cervical cancer patients aged 60 and above in Denmark in 2009-2013 found the average age of non-screened patients to be 76 years, in line with the current second top on the incidence curve [2].…”
Section: Introductionmentioning
confidence: 71%
“…It should, however, be taken into account that after 50 years of screening, the current age-specific incidence of cervical cancer is no longer a pure reflection of the underlying risk of the disease, but it reflects also the screening history of the respective birth cohort. A study of cervical cancer patients aged 60 and above in Denmark in 2009-2013 found the average age of non-screened patients to be 76 years, in line with the current second top on the incidence curve [2].…”
Section: Introductionmentioning
confidence: 71%
“…Besides, the inadequate early cervical screening in patients aged ≥65 possibly delayed the diagnosis and deteriorate the prognosis. 14,15 Regular cervical screening in patients above 65 years old helps reduce the incidence of cervical cancer by 75% and the mortality of the disease. 16 Therefore, deficiency of typical clinical features and cervical screening might contribute to late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality in older women may be a result of a high proportion of advanced stage disease, high comorbidity and a high level of frailty, which likely affects the choice of treatment. Thus, older women are less likely to undergo radical surgery and receive external beam and intra‐cavitary radiation, which may affect their survival rate.…”
Section: Discussionmentioning
confidence: 99%